An evening milk drink can affect word recall in Indonesian children with decreased sleep efficiency: A randomized controlled trial. (14th September 2018) - Sekartini, Rini; Chandra, Dian Novita; Arsianti, Tiana; Bardosono, Saptawati; Wiguna, Tjhin; Schaafsma, Anne
Abstract : Study objectives: Sleep is important for memory consolidation in children. This study intended to find out whether an evening milk-based drink could influence sleep efficiency and memory recall in a group of Indonesian children (5–6 years old) with sleep deprivation. Methods: Children were randomly allocated to one of three interventions: Reference product, satiety-stimulating product, and a relaxing product. The intervention lasted for 6 weeks and children consumed two servings per day of each 200 ml, the serving in the morning being the same for all children. All measurements took place at baseline and at the end of the intervention. Sleep parameters were studied using actigraphy and a sleep diary during three consecutive days. Memory consolidation was tested using a 20 word-pair list, which was memorized the evening before being recalled the next morning at home-base. Anthropometry was measured using standard equipment. Results: The Satiety group showed a significant decrease in word recall, and a significant increase in nocturnal awakenings that was inversely associated with sleep efficiency at the end of the intervention. Sleep efficiency did not differ between the three groups being 75.5 ± 8.6% and 75.7 ± 6.3% at baseline and end of the intervention, respectively. Despite the lower energy intake in the Standard (reference) group, this condition showed the highest increase in weight. Discussion: Evening growing-up milks can affect memory recall, sleep characteristics, and growth. However, to correct sleep efficiency and sleep duration, improvement of parental behavior may be the most important factor with nutrition providing a supplementary effect.